Sustainable coffee capsule consumption: Understanding Italian consumers' purchasing drivers - Samoggia, Antonella; Busi, Riccardo (Frontiers in Sustainable Food Systems, 2023)
Coffee is among the most appreciated beverages by consumers globally. Single serve coffee market expands and is highly profitable, but coffee in capsules (CIC) raises a major issue of environmental sustainability. The coffee industry aims to expand the CIC sales and to reduce capsule environmental impact and waste. To better define a sustainability-oriented strategy, the coffee industry needs to understand how to approach different socio-economic consumer groups. Thus, this study aims to explore consumers’ perception and awareness of sustainable CIC, with specific attention on consumers’ socio-economic characteristics. The study interviewed a sample of 261 Italian consumers. Data elaboration includes four main steps: a cluster analysis leading to three socio-economic groups, a factor and structural equation modelling to confirm the factors and the relation between CIC sustainability and quality factors, and a multinomial logistic regression to examine the factors that drive the likeliness of consumers’ willingness to purchase sustainable CIC. Results support that all groups of consumers value sustainability attribute as main CIC purchasing decision driver. The sustainability factor does not show any significance on the explanation of the CIC quality factor. Consumer perception of the CIC sustainability is not affected by age, income, level of education, and gender. This study provides preliminary insights for sustainable CIC production and consumption.